Komparasi Nilai Filosofis Musik Senggayung Dayak Pesaguan dan Semboyan Adil Ka’ Talino, Bacuramin Ka’ Saruga, Basengat Ka’ Jubata - Ranubaya, Fransesco Agnes; Endi, Yohanes (Balale' : Jurnal Antropologi, 2024)
The Dayak Philosophy "Adil Ka' Talino, Bacuramitn Ka' Saruga, Basengat Ka' Jubata" and Senggayung music have a close relevance in the context of culture, identity, spirituality, and creative expression of the Pesaguan Dayak tribe. The purpose of this study is to determine the meaning of Pesaguan Dayak Senggayung Music in the Light of the Philosophy of "Adil Ka' Talino, Bacuramitn Ka' Saruga, Basengat Ka' Jubata" and its relevance to the lives of Dayak indigenous people in general. The methodology used in this paper uses qualitative research that is done through a phenomenological point of view. The findings in this study that the meaning of Pesaguan Dayak Senggayung Music according to the light of the "Adil Ka' Talino, Bacuramitn Ka' Saruga, Basengat Ka' Jubata" philosophy is so profound and relevant in the lives of Dayak people in general. This research is very contextual to the current situation, especially for the younger generation to love culture and philosophical thoughts from their own culture so that the same desire arises to maintain and preserve Dayak cultural customs with full awareness.